Sentidos e significados das práticas educativas de mães de crianças com transtorno do déficit de atenção e hiperatividade(tdah) sob o olhar da psicologia social comunitária - Portella, Roseni Aparecida (2016)
This study aimed to understand the meanings of the educational practices of mothers of children diagnosed with Attention Deficit Hyperactivity Disorder - ADHD. The theoretical framework is based on Vygotsky's discussion of sense and meaning and theory of subjectivity González-Rey. It is a qualitative study with semi-structured and analyzed by purporting meaning cores interviews. Knowledge of this research will be used to guide the planning of a group of social support to these mothers. The results indicated that the main way evidenced by the mother, protection, a mobilizing anxiety, recognition of subjectivity and abilities of children. The difficulties and the action strategies and the meanings of educational practices given by the mother are important contributions to addressing the construction of a group of social support to these mothers. Emerged from the analysis of the interviews some important topics such as the feeling of workload and responsibilities of these mothers, lack of support networks and the willingness to participate in groups of mothers, the difficulties of standardized education system, medical appeal and schools as the medicalization and anxiety of mothers and social exclusion of their children, which is a key driver of anxieties about the future. It therefore think of the role of educators and students, with a close eye to the relations established in society, parent-child interaction / teacher-student, continually rethinking the educational practices, since society is not static and education need to track your movement , their transformation.